AN ANALYSIS OF STUDENTS' DISFLUENCY FACTORS IN SPEAKING ABILITY AT THIRD SEMESTER ENGLISH STUDY PROGRAM STUDENTS - Putri Buana; Ririn Putri Ananda (Teaching English and Language Learning English Journal, 2022)
The research objectives were to know the students’ disfluency factors in speaking ability and to know the dominant students’ disfluency factor in speaking ability at third semester English Study Program. This research was a descriptive quantitative research which aimed to find out the students’ disfluency factors in speaking ability at third semester English Study Program. Subject of the research was the whole students at third semester English Language Education Study Program of UMB Academic Year 2020/2021. The total subjects were 11 students who got score < 60 in fluency test. The instruments of this research were fluency test and questionnaire. The fluency test was used to measure the students’ fluency level in speaking English. The questionnaire consisted of some questions related to the students’ disfluency factors. The questionnaire was adopted from Wang (2014) theory. There were two findings of this research; first, the students’ disfluency factors in speaking ability at third semester English Study Program of UMB were cognitive factor, linguistic factor, and affective factor; second, the most dominant disfluency factors in speaking ability at third semester English Study Program of UMB was linguistic factor. Based on the result of this research, the research result found that linguistic factor becomes the most dominant disfluency factor affected the students’ speaking ability. It was suggested for the students to master vocabulary and grammar in English since the linguistic factor related to the vocabulary and grammar skill. Key words: Disfluency Factors, Speaking Ability